Medical benefit for the foreign workers on Malaysia / Nur Zafirah Rosli … [et al.] - Rosli, Nur Zafirah; Ismail, Masliela; Mohd Rozit, Siti Ruwaida; Mohd Roslan, Yuhanis (2010)
Malaysia has an influx of foreign workers because of its economic development. The standard of medical benefit for foreign workers has been specified by the International Labour of Organization. In line with those standards, foreign workers in Malaysia have been provided with medical benefits under the workmen's Compensation Act 1952 and other legislation. This research will look into the definition of medical benefit under the various law of Malaysia that intends to protect foreign workers of their rights towards medical benefit. This research aims to overcome the non compliance of the employers in providing medical benefits and insurance for their foreign workers. The lack of awareness of Malaysian employers of the rights of foreign workers medical benefit has caused them to seek medical treatment at public hospital. The public outcry of long waiting list has lead to this research. A survey conducted on foreign workers seeking medical treatment at the hospital has revealed the non compliance of the Malaysian employers as to the medical benefit of the foreign workers. This research looks into the practice by the Government of Singapore in ensuring the compliance of the rights of foreign workers to medical benefits as required by the International Labour Organization, such as the provisions of Medisave, Medifund and MediShield. The research thereby proposed a collaboration between the three ministries in Malaysia that deals with the foreign workers namely, Ministry of Human Resource, Ministry of Home Affairs and Ministry of Health to ensure that Malaysia comply with the provision of medical benefits for its foreign workers as in Singapore. Apart from that, this research also proposed the establishment of one stop training centre to educate the Malaysian employers of the rights of the foreign workers of their medical benefits.